Identifikasi faktor kontrak psikologis, organisasi politik dan komitmen organisasi terhadap kinerja karyawan manufaktur PT ZYX - Mardiana, Yanthy; Suyudi, Wahidiyat; Hertina, Dede; Rizki, Muhammad Irfan (Jurnal Ilmu Manajemen, 2024)
The essence of this research is to examine the influence of organizational commitment, organizational politics, and psychological contracts on employee performance. On the basis of this research, the survey sample was taken from employees in the production department of PT ZYX. The population and sample of this research are employees in the After Sales division of PT. ZYX, with a total of 100 respondents. The analytical method used in this case is white`s Robust standard error regression analysis and the data used is primary data obtained from questionnaires distributed to all employees. Based on the research results, it shows that the psychological contract and organizational commitment have a significant effect on employee performance, while organizational politics have an insignificant effect. If viewed simultaneously, all independent variables (contract, psychology, organizational commitment and organizational politics) have a significant influence on employee performance.